(untitled) (Journal of the College of Basic Education, 2020)
The importance of the research to identify the impact of training to develop the skills of the crushing blow and blow-hammering using cross training. The researcher was able to work on this subject and to take advantage of the results of this study and improve it to help the training process, especially in the courses of badminton training. The problem of research became apparent after the researcher studied most of the training curricula. Although badminton requires a coach to take into consideration the speed of the feather and its versatility. A very important problem. The study aimed to prepare training according to the cross-training method to develop the skills of the overwhelming blow and flying feathers. The researchers used the style of the experimental group, both tribal and remote, to suit the nature of the problem. The random sample was chosen by drawing lots and the selection of the 10 club was recommended. The trained researchers and the players recommended the importance of using Cross training and use for other categories